2020
DOI: 10.18410/jebmh/2020/80
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Health and Hygiene- Study of Knowledge Attitudes and Practices of Obgyns on Usage of Menstrual Cups

Abstract: BACKGROUNDMeagre data exists as to whether health care professionals consider and advocate menstrual cups as a safe and feasible alternative to the generally used methods of menstruation management. The attitudes and practice among girls and women with respect to usage of menstrual cups is also not known. Therefore, we conducted a cross-sectional survey to understand the knowledge, attitudes and practices of menstrual cup and its recommended usage from the health care providers dealing with young girls and wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Based on the study by Divakar et al [ 18 ], assuming 56% of the respondents would feel the menstrual cup is a better alternative, with 20% relative precision and 5% alpha error, the sample size was estimated to be 76. Considering the sensitive issue and non-response rate of 25%, a total of 101 participants were recruited.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the study by Divakar et al [ 18 ], assuming 56% of the respondents would feel the menstrual cup is a better alternative, with 20% relative precision and 5% alpha error, the sample size was estimated to be 76. Considering the sensitive issue and non-response rate of 25%, a total of 101 participants were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the study by Divakar et al [18], assuming 56% of the respondents would feel the menstrual cup is a better alternative, with 20% relative precision and 5% alpha error, the sample size was estimated to be 76.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Pads and tampons are mostly made of synthetic material like rayon, it's effects have on the human body are much more severe than just superficial irritation and allergy. 2,3 Socio-culturally based research study find different myths and misconceptions related to menstruation. 4 In lower and middle-income countries, because of social issues and lack of guidance maximum of the girls experience fear, confusion, shame, and discomfort while they try to be habitual to their monthly period.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 43% to 88% of the women still wash their cotton cloths and reuse them instead of using disposable pads. 6 Sanitary pads and napkins are the most common practices, but they require hygienic practices; otherwise, they may cause the highest risk of reproductive tract infections among girls. The girl's stigma related to menstruation is quite worrying but by providing proper menstrual hygiene knowledge stigma will gradually reduce.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that in India, 62% of the young women in the age group of 15 years to 24 years still use clothes for their menstrual protection. Approximately, 43% to 88% of the women still wash their cotton cloths and reuse them instead of using disposable pads [3] . In rural areas maintenance of menstrual hygiene is, therefore, is an important yet unrecognized issue.…”
Section: Introductionmentioning
confidence: 99%